Identification of interaction between serotonin transporter and glycogen synthase kinase-3ββ gene polymorphisms: role in susceptibility to bipolar disorder. (May 2009) - Subhashree, D; Kiran Kumar, HB; Purushottam, Meera; Shubha, GN; Vallikiran, M; Krishna, Nithin; Sriharsha, J; Reddy, YCJ; Ghosh, Saurabh; Mukherjee, Odity; Jain, Sanjeev
Background: Genetic correlates of diseases of complex inheritance may include variations in several genes lying within a network of linked biological processes. Synaptic mechanisms, such as serotonin neurotransmission and second (third) messengers (e.g., glycogen synthase kinase [GSK]), have been implicated in susceptibility to mood disorders, the actions of therapeutic drugs and manipulation of circadian rhythms. A better understanding of such gene networks may be useful to understand the biology and treatment of mood disorders.Methods: We studied the association between serotonergic and GSK-mediated signaling networks with bipolar affective disorder (BPAD). We analyzed two single nucleotide polymorphisms (SNPs) in the HTR2A gene, a promoter SNP in SLC6A4 and a promoter SNP in the GSK3 B gene in BPAD individuals and matched controls. A multifactor dimensionality reduction tool was employed to study gene––gene interactions and analyze multilocus genotype combination associations with high- or low-risk of BPAD.Results: Multifactor dimensionality reduction detected the best interacting model involving 5-HTTLPR ( SLC6A4 ) and rs334558 ( GSK3B ).Conclusion: Our results suggest interplay between the serotonergic pathway and the second-messenger system involving GSK, which are important drug targets.